Assessment of a 16S rRNA amplicon Illumina sequencing procedure for studying the microbiome of a symbiont‐rich aphid genus. (1st November 2015) - Jousselin, E.; Clamens, A.‐L.; Galan, M.; Bernard, M.; Maman, S.; Gschloessl, B.; Duport, G.; Meseguer, A. S.; Calevro, F.; Coeur d'acier, A.
Abstract: The bacterial communities inhabiting arthropods are generally dominated by a few endosymbionts that play an important role in the ecology of their hosts. Rather than comparing bacterial species richness across samples, ecological studies on arthropod endosymbionts often seek to identify the main bacterial strains associated with each specimen studied. The filtering out of contaminants from the results and the accurate taxonomic assignment of sequences are therefore crucial in arthropod microbiome studies. We aimed here to validate an Illumina 16S rRNA gene sequencing protocol and analytical pipeline for investigating endosymbiotic bacteria associated with aphids. Using replicate DNA samples from 12 species (Aphididae: Lachninae, Cinara ) and several controls, we removed individual sequences not meeting a minimum threshold number of reads in each sample and carried out taxonomic assignment for the remaining sequences. With this approach, we show that (i) contaminants accounted for a negligible proportion of the bacteria identified in our samples; (ii) the taxonomic composition of our samples and the relative abundance of reads assigned to a taxon were very similar across PCR and DNA replicates for each aphid sample; in particular, bacterial DNA concentration had no impact on the results. Furthermore, by analysing the distribution of unique sequences across samples rather than aggregating them into operational taxonomic units (OTUs), we gained insight into the specificity of endosymbionts for their hosts. Our results confirm that Serratia symbiotica is often present in Cinara species, in addition to the primary symbiont, Buchnera aphidicola . Furthermore, our findings reveal new symbiotic associations with Erwinia‐ and Sodalis‐ related bacteria. We conclude with suggestions for generating and analysing 16S rRNA gene sequences for arthropod‐endosymbiont studies.